Quantum Dot Cadmium Selenide As A Saturable Absorber For Q-Switched And Mode-Locked Double-Clad Ytterbium-Doped Fiber Lasers - Mahyuddin, Mohamad Badrol Hisyam; Abdul Latiff, Anas; Mohd Rusdi, Muhammad Farid; Irawati, Ninik; Harun, Sulaiman Wadi (Elsevier B.V., 2017)
This paper demonstrates the integration of quantum dot (QD) cadmium selenide (CdSe) nanoparticles, which is embedded into polymethyl methacrylate (PMMA) film into an ytterbium-doped fiber laser (YDFL) cavity to produce Q-switched and mode-locked fiber lasers. The QD CdSe based film functions as a saturable absorber (SA). For Q-switching operation, stable pulse is generated within 970–1200 mW pump power, with tunable repetition rate and pulse width of 24.5–40.5 kHz and 6.8–3.7 μs, respectively. Maximum pulse energy and peak power are obtained about 1.1 μJ and 0.28 W, respectively. As we tune the polarization state of the laser cavity and use a single QD CdSe film, the mode-locking operation could also be generated within 310–468 mW pump power with repetition rate of 14.5 MHz and pulse width of 3.5 ps. Maximum pulse energy and peak power are obtained about 2 nJ and 0.11 W, respectively. These results may contribute to continuous research work on laser pulse generation, providing new opportunities of CdSe material in photonics applications.